Orexinergic neurons modulate stress coping responses in mice - Kim, Jae Gon; Ea, Ji Yun; Yoon, Bong-June (Frontiers in Molecular Neuroscience, 2023)
Stress is a critical precipitating factor for major depression. However, individual responses to the same stressor vary widely, possibly owing to individual variations in stress resilience. Nevertheless, the factors that determine stress susceptibility and resilience remain poorly understood. Orexin neurons have been implicated in the control of stress-induced arousal. Therefore, we investigated whether orexin-expressing neurons are involved in the regulation of stress resilience in male mice. We found that the level of c-fos expression was significantly different in susceptible versus resilient mice in the learned helplessness test (LHT). Furthermore, activating orexinergic neurons induced resilience in the susceptible group, and this resilience was also consistently observed in other behavioral tests. However, activating orexinergic neurons during the induction period (during inescapable stress exposure) did not affect stress resilience in the escape test. In addition, analyses using pathway-specific optic stimulation revealed that activating orexinergic projections to the medial part of the nucleus accumbens (NAc) alone mediated a decrease in anxiety but was not sufficient to induce resilience in the LHT. Collectively, our data suggest that orexinergic projections to multiple targets control diverse and flexible stress-related behaviors in response to various stressors.